Krik? Krak! - Danticat, Edwidge, 1969- (New York : Vintage Books, 1996)
When Haitians tell a story, they say "Krik?" and the eager listeners answer "Krak!" In Krik? Krak! In her second novel, Edwidge Danticat establishes herself as the latest heir to that narrative tradition with nine stories that encompass both the cruelties and the high ideals of Haitian life. They tell of women who continue loving behind prison walls and in the face of unfathomable loss; of a people who resist the brutality of their rulers through the powers of imagination. The result is a collection that outrages, saddens, and transports the reader with its sheer beauty.
Keywords: Haitian Americans -- Fiction; Manners and customs -- Fiction; Women -- Haiti -- Fiction; Girls -- Haiti -- Fiction; Haiti -- Fiction